Teori-teori terminologi: deskripsi, preskripsi dan penjelasannya (Jurnal Bahasa, 2006)
During the past decade, the theory of terminology has been a subject of debate in various circles. This article examines some of the reasons why this topic has been receiving so much interest lately. I will first discuss the theory developed by Mister and analyse the motivations behind his model. Then, I will explain why the Wiisterian theory was not questioned or challenged for a long time. This will lead us to the reasons why so many critical voices have been raised recently, both from inside traditional viewpoints and outside. I will also look at the reception these new ideas have had in terminology circles. Finally, I will present my own definition of a theory of terminology, by examining important issues such a theory should take into account and see what I can offer to this debate.